A techno-economic assessment of landfill gas emissions and energy recovery potential of different landfill areas in Turkey. (1st December 2020) - Kale, Cihangir; Gökçek, Murat
Abstract: Landfills are a widespread application for the management of municipal solid waste and the production of energy. However, landfill gas estimations, analysis of its energy capacity, and economic analyses need to be performed properly for a landfill project area. Although there are many gas prediction models in the literature, the default values in the model such as the methane production capacity ( L o ) and the methane production rate ( k ) need to be recalculated according to the climate and waste composition of the region in order to obtain a more accurate gas estimation. Furthermore, the energy project from waste is expected to evaluate the through lifetime with variables (landfill operation, gas collection efficiency, different combustion engines, etc.) for an optimum plant capacity. In this study, it is aimed to investigate the landfill gas and methane production potential that can be obtained in landfill areas in different provinces of Turkey and to determine an optimum plant capacity by performing energy production cost analysis. To achieve this, the LandGEM 3.02 version was used to estimate long-term landfill gas potential in this study. The L o value was calculated by using the IPCC (Intergovernmental Panel on Climate Change) methodology, and the k value was determined by considering the meteorological data of the regions (precipitation amount, etc.). The future population of the selected regions was estimated using the arithmetic increase method. According to this estimation, the solid waste quantity to be generated in the future was calculated. Energy capacities of these areas were calculated using internal combustion reciprocating engines with six different capacities. The unit energy production cost was evaluated by employing the levelized cost method. The optimum plant capacity was found by evaluating the energy production costs obtained for each site and six different engines. As a result, it is observed that the energy production plant with the optimum capacity determined from waste is economically and ecologically feasible. Graphical abstract: Image 1 Highlights: The landfill gas was estimated for landfill areas in different scale. Energy production potential were calculated in engines with different capacity. The analysis for sites were carried out as economically and environmentally. . Landfill energy projects are economically and technically reasonable. The landfill offers a good waste reduction and clean energy recovery alternative.